The influence of cantilever length and implant angulation in completely edentulous patients using the finite element analysis and the All-on-four/Fast & Fixed treatment concept - A review of the literature - Raluca-Gabriela Mocanu; Cristina Teodora Preoteasa; Daniela Meghea; Elena Preoteasa; Laurentiu-Iulian Florica; Sebastian-Robert Mocanu (Amaltea Medical Publishing House, 2020)
Aim. The purpose of this literature review is to provide an overview of the finite element analyses on All-on-four and Fast & Fixed treatment concept, regarding the dimension of the distal cantilever and the degree of implant tilting. Material and methods. An electronic search including major medical data bases as: PubMed (Medline), Google Academic, Semantic Scholar, Elsevier, Science Direct, Wiley Online Library. The following searching terms were used: finite element analysis, implant cantilever length, tilted implants. Results. Eight articles were selected for this review. According to their results, a value between 30 and 45 degrees in angulation and a minimal cantilever length represents the best way to elaborate the final prosthetic restorations. Conclusion. The common opinion of all the research studies included is that whenever the implant angulation increases and the dimension of the cantilever decreases, the clinical outcomes will be favorable and predictable.